LEADERSHIP WHOISM: AN INSIGHT INTO THE LOGIC OF GOOD LEADERSHIP (American Journal of Research in Humanities and Social Sciences, 2023)
This research with the title, Leadership Whoism, is aimed at unraveling the essential fundamental criterion that ought to define the person or the whoism of a leader. This work makes reference to the thoughts of the Golden Triad on leadership in situating its philosophical framework through which it justifies its thesis which asserts that an absolutely necessary nexus exists between the possession of virtues and functioning as a leader. The pivotal problem which inspires this discourse is the enigma of moral turpitude which poses a daunting challenge to actors in the leadership arena. This problem is best captured in the inquisitives or questions of this research: who ought to be a leader? Is leadership an all-comers affair? Through an intrepid assessment of the ideas of the Golden Triad on leadership, the research addresses the first question by positing the categorical fundamental criterion for becoming a leader and answers the second inquisitive in the negative by asserting that leadership should be accorded only those who possess virtues. In its conclusion, the work unveils the conjunctive logical formular for good leadership and submits that the operationalization of the virtue-cum- leadership correspondence tenet adumbrated by the triad thinkers will flatten the steeping curve of leadership morass which has become an intractable pandemic to humanity. This research is thus very significant in that it reflects the urgency of articulating a ramified knowledge structure and cognitive parameters for leadership conversation on who ought to be a leader.